Ethno-Project Based Teaching Module to Increase Student Creativity - I Gusti Ayu Agung Sinta Diarini; Ni Kadek Widyastuti; Putu Andyka Putra Gotama; I Made Ari Winangun (Jurnal Pendidikan dan Pengajaran, 2024)
This research is motivated by obstacles to implementing an independent curriculum in the learning process. These obstacles are mastery of digital technology as a standard for the independent curriculum and understanding the relationship between several main components. This research aims to produce a development product in the form of an ethno-project-based teaching module in learning Hospitality Basics that is valid, practical, and effective for increasing student creativity. The research method used in this research is the research and development of the ADDIE model. The subjects in this research were 39: 2 judges to assess product validity in terms of content and culture aspects, 1 teacher and 5 students to assess product practicality, and 31 students to test the effectiveness of product development implementation. Instruments and data collection techniques were carried out by administering questionnaires to research subjects at the Develop stage and pretest and posttest at the Implement stage. Data analysis techniques were carried out descriptively, quantitatively, and inferentially. Based on the data analysis carried out, it can be concluded that the ethno-project-based teaching module in learning Hospitality Basics in housekeeping and public area material has very good validity so that it can be implemented in the learning process; the ethno-project-based teaching module is efficient to use in facilitating the process learning and ethno-project based teaching modules are pretty effective in increasing student creativity.